Quasiparticle electronic band structure of the alkali metal chalcogenides - Syrotyuk, S.V.; Shved, V.M. (Condensed Matter Physics, 2015)
The electronic energy band spectra of the alkali metal chalcogenides M₂A (M: Li, Na, K, Rb; A: O, S, Se, Te) have been evaluated within the projector augmented waves (PAW) approach by means of the ABINIT code. The Kohn-Sham single-particle states have been found in the GGA framework. Further, on the basis of these results the quasiparticle energies of electrons as well as the dielectric constants were obtained in the approximation GW. The calculations based on the Green's function have been originally done for all the considered M₂A crystals, except Li₂O. Електроннi енергетичнi спектри халькогенiдiв лужних металiв M₂A (M: Li, Na, K, Rb; O, S, Se, Te) були пiдрахованi за методом проекцiйних приєднаних хвиль (PAW) за допомогою програми ABINIT. Одночастинковi
стани у формалiзмi Кона-Шема були знайденi в рамках GGA (узагальнене градiєнтне наближення). Далi на
основi цих результатiв були отриманi квазiчастинковi енергiї електронiв та дiелектричнi константи у наближеннi GW. Для розглянутих кристалiв M₂A розрахунки на основi функцiї Грiна були зробленi вперше,
за винятком Li₂O.